2019
DOI: 10.1016/j.whi.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Community Perspectives on Contraception in the Context of the Zika Virus in the U.S. Virgin Islands: Implications for Communication and Messaging

Abstract: Background: Between January and October 2016, 575 symptomatic confirmed cases of Zika virus infection were reported in the USVI. Zika virus infection during pregnancy can cause serious birth defects. Preventing unintended pregnancy among women who choose to delay or avoid pregnancy is a primary strategy to reduce these adverse outcomes.Methods: A rapid assessment, using one men's and five women's focus groups (N=43), was conducted to inform communication efforts to increase awareness of contraception as a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Twelve papers were found in the database search, and one in other sources. 35 With regard to the general characteristics of the included papers, the type of infectious disease outbreak varied between dengue fever (n=4), 36–39 Ebola virus disease (n=1), 40 Zika-virus (n=1) 41 and H1N1 influenza (n=4). 42–45 In addition, three papers used scenario simulations about an influenza A pandemic instead of actual outbreaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve papers were found in the database search, and one in other sources. 35 With regard to the general characteristics of the included papers, the type of infectious disease outbreak varied between dengue fever (n=4), 36–39 Ebola virus disease (n=1), 40 Zika-virus (n=1) 41 and H1N1 influenza (n=4). 42–45 In addition, three papers used scenario simulations about an influenza A pandemic instead of actual outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations on the use of social media and local radio programmes to disseminate information were directly implemented in a community communication campaign about Zika virus. 41 Second, for papers with a national approach, the views of the public were not directly used to change OM practice but were formulated as recommendations for future policy. 35 42 44 46 47 This also applied for the studies using pandemic simulation scenarios, instead of an actual outbreak.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles [28][29][30][31][32][33][34][35][36][37][38][39], six of which were original research papers [28,30,[33][34][35]37], gave insight into communication with the public during disasters. Health communication campaigns spread through billboards, the radio, newspaper adverts, and social media and sexual education programs were used by health providers to provide information on how the Zika virus spreads [21,31,32,[34][35][36]. However, message content for the public on the modes of transmission of Zika and recommendations to use condoms in Zika-affected areas was found to not be strong enough [36,37].…”
Section: Importance Of Contraception During Disastersmentioning
confidence: 99%
“…Nineteen articles [21,34,75,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113], eleven of which were original research studies [21,34,99,101,103,[106][107][108][109][110]113], considered how demand for contraception changed. There was conflicting evidence on whether the Zika outbreak led to increased demand for contraception [21,34,110]. Similarly, while some women reported that they wanted to delay childbearing during the COVID-19 pandemic and considered use of LARC, others did not change their views [75].…”
Section: Barriers To Use Of Contraception During Disastersmentioning
confidence: 99%
“…While Zika infection rates have rapidly declined, recent localized outbreaks highlight the need for continued communication with the public about prevention of all mosquito-borne diseases [World Health Organization (WHO), 2019b]. Responding to viruses transmitted by mosquitoes, such as Zika, dengue, chikungunya, yellow fever, and others, are often a challenge to address due to the pressure that outbreaks place on health resources, difficulty engaging communities, insufficient regional expertise and capacity, and complicated logistics [Maciel-de-Freitas et al, 2012;Horstick et al, 2010] Research regarding health communication in affected countries emphasizes the need for accurate and efficient communication between public officials, medical personnel, and the public, including the need to tailor dissemination methods to communities and provide culturally relevant information [McNeish et al, 2019;Brittain et al, 2019].…”
Section: Introductionmentioning
confidence: 99%